Chicken Soup For The Soul : Think Positive : 101 Inspirational Stories About Counting Your Blessings and Having a Positive Attitude - Canfield, Jack( 1944-); Hansen, Mark Victor; Newmark, Amy; Norville, Deborah
A collection of 101 true personal stories from regular people about the power of positive thinking in their lives and how they use positive thingking, count their blessings, and are grateful.